2007
DOI: 10.1097/shk.0b013e3180311e60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brain Cooling on Brain Ischemia and Damage Markers After Fluid Percussion Brain Injury in Rats

Abstract: Although systemic cooling had recently been reported as effective in improving the neurological outcome after traumatic brain injury, several problems are associated with whole-body cooling. The present study was conducted to test the effectiveness of brain cooling without interference with the core temperature in rats after fluid percussion traumatic brain injury (TBI). Brain dialysates ischemia (e.g., glutamate and lactate-to-pyruvate ratio) and injury (e.g., glycerol) markers before and after TBI were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…7 In brain-injured patients, however, it has not been clearly demonstrated that normothermia attenuates brain damage, and the exact mechanisms by which this may occur are only beginning to be elucidated. Although treatment of fever is routine in neurocritical care, proof of principle and clinical benefit have yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…7 In brain-injured patients, however, it has not been clearly demonstrated that normothermia attenuates brain damage, and the exact mechanisms by which this may occur are only beginning to be elucidated. Although treatment of fever is routine in neurocritical care, proof of principle and clinical benefit have yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…of 8 rats per group. cerebral infarct and motor dysfunction were found to be associated with both an increase in intracranial pressure and a decrease in cerebral perfusion pressure during traumatic brain injury (Chio et al, 2007). The decrease in cerebral perfusion pressure (=mean arterial pressure − intracranial pressure) is due to an increase in intracranial pressure because an appropriate level of mean arterial pressure is maintained after traumatic brain injury.…”
Section: Discussionmentioning
confidence: 98%
“…There is in vitro 2 and overwhelming animal 4 evidence that mild hypothermia provides substantial protection against tissue ischemia. Although the amount of protection varies with the model, several degrees of hypothermia typically provide factor-of-three benefits.…”
Section: Potential Benefits Of Therapeutic Hypothermiamentioning
confidence: 99%
“…The first is in asphyxiated neonates. 4,5 It is easy to cool infants-in fact, the difficulty is usually preventing hypothermia. Mild hypothermia is thus rapidly being adapted as the therapeutic choice for asphyxiated neonates.…”
Section: Potential Benefits Of Therapeutic Hypothermiamentioning
confidence: 99%